Cultural values orientation in the movie “The Architecture of Love” - Parasian, Nehemia Anugrah; Perangin-angin, Alemina Br. (Priviet Social Sciences Journal, 2025)
This research is entitled Cultural Value Orientation in the Movie “The Architecture of Love.” This research aims to represent cultural values in the film based on Kluckhohn's view that cultural value orientation is divided into five categories: human nature, man nature, time, activity, and relational. This research used a descriptive qualitative approach. Data collection techniques were carried out through observation, documentation, and literature studies. Data analysis was performed by observing the film from beginning to end, focusing on the cultural values of Kluckhohn's thoughts, namely, scenes and dialogues in the film The Architecture of Love that represent cultural values. Based on data analysis, five data were found including human nature, five data were man nature orientation, four data were time orientation, four data were activity orientation, and four data were relational orientation. The film represents complex and interrelated cultural values, reflecting the dynamics of human life in a modern context. Using Kluckhohn’s cultural value analysis approach, this movie reveals how individuals deal with trauma, rebuild themselves, and establish relationships within the framework of certain cultural values.